Certain properties for a class of analytic functions associated with hypergeometric functions - Khadeejah R. Alhindi; Maslina Darus (Journal of Numerical Analysis and Approximation Theory, 2014)
In this particular paper, we investigate coefficient inequalities, closure theorems, convolution properties for the functions belonging to the class \( \mathcal{S}^{m,r,s}_{λ_1,λ_2}(η)\). Further, integral transforms of functions in the same class are also discussed.